Penentuan Arah Kiblat Secara Partisipatif di Kampung Pasir Panjang - Farouki Dinda Rassarandi; Siti Noor Chayati; Oktavianto Gustin; Luthfiya Ratna Sari; Sudra Irawan; Arif Roziqin; Wenang Anurogo; Muhammad Zainuddin Lubis; Nur Cahyono Kushardianto; Dodi Prima Resda; Agung Riyadi; Supardianto Supardianto; Sandi Prasetyaningsih; Condra Antoni; Rizki Widi Pratama; Rizki Irianto; Dicki Prayogi; Rizwan Bin Khamis; Bintang Budhiman (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
Qibla is the center of direction for Muslims in performing prayer services. In equatorial regions such as Indonesia, an error in determining the Qibla direction of just 1o can make the direction deviate as far as 111 km from the Kaaba. This community service activity aims to socialize the method of determining the direction of Qibla with mapping survey technology, namely Total Station, as well as together with the local community to carry out measurement activities in the field. Community service activities have been carried out in two stages, namely preparation and implementation in the field. Pre-implementation activities include site surveys and preparation of equipment to be used in the field. By using the principle of calculating the spherical triangle in Geodesy Mathematics and utilizing the development of accurate positioning technology, the Total Station and compass are used to measure the Qibla direction after previously correcting the true north with the help of celestial bodies such as the sun. Thus, the measurement results obtained will have good accuracy. From the measurement of the Qibla direction that has been done at the Nurus Sabil mosque, the angle of Qibla direction from north to west is obtained by 66o 50' 59.83" or compass azimuth of 293o 9' 0.17 ". Based on the results of these calculations there are differences in the azimuth of 12° from the azimuth / direction of the mosque's initial Qibla there. This happens because indeed the mosque from its inception has never been carried out the determination and confirmation of the direction of Qibla carefully and officially.